A Longitudinal Study of Plasma and Urinary Cortisol in Pregnancy and Postpartum - Jung, Caroline; Ho, Jui T.; Torpy, David J.; Rogers, Anne; Doogue, Matt; Lewis, John G.; Czajko, Raymond J.; Inder, Warrick J. (The journal of clinical endocrinology and metabolism, 2011)
Context:There is a paucity of longitudinal data on plasma and urinary cortisol levels during pregnancy using modern assays. Furthermore, conflicting data exist as to the effect of the low-dose oral contraceptive pill (OCP) on cortisol.Design, Subjects, and Measurements:We conducted a prospective longitudinal study on morning plasma cortisol (total and free), corticosteroid-binding globulin (CBG), and 24-h urinary free cortisol (UFC) levels in 20 pregnant women during the first, second, and third trimesters and 2–3 months postpartum compared with 12 subjects on low-dose OCP and 15 nonpregnant subjects not taking the OCP (control group).Results:A progressive rise in total plasma cortisol, CBG, and 24-h UFC was demonstrated during pregnancy, peaking during the third trimester (mean 3-fold rise compared with controls). Plasma free cortisol increased 1.6-fold by the third trimester. In the OCP group, total plasma cortisol and CBG were 2.9- and 2.6-fold elevated, respectively, whereas 24-h UFC and plasma free cortisol were not significantly different from controls. Compared with liquid chromatography-mass spectrometry, a commercial immunoassay underestimated mean total plasma cortisol concentrations by 30% during second and third trimesters and in OCP users and overestimated UFC levels by 30–35% during pregnancy.Conclusions:Our study demonstrated elevations in total plasma cortisol and CBG concentrations during pregnancy and with low-dose OCP use. Pregnancy was also associated with significant increases in plasma free cortisol and UFC, suggesting that the rise in total plasma cortisol is contributed to by up-regulation of the maternal hypothalamic-pituitary-adrenal axis in addition to elevated CBG.